Nondescent vaginal hysterectomy: analysis of indications and complications - Patil, Shashikala B; A, Saravana; Patil, Savita S; Shankaregowda, H. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the commonest major surgical procedure performed in gynecology. It can be done by abdominal or vaginal route and with the help of laparoscopy. Laparoscopic assisted vaginal hysterectomy (LAVH) and total laparoscopic hysterectomy (TLH) although gaining more popularity now a days, though it is associated with higher cost, longer duration of operation, and need general anaesthesia. The latest value study concluded that major haemorrhage, hematoma, ureteric injury, bladder injury, and anesthetic complications were more in laparoscopic assisted hysterectomy (LAVH) group when compared to abdominal and vaginal hysterectomies. In addition LAVH was accomplished in twice the time required for vaginal hysterectomy.The objective of the study was to analyse the indication and to study the complications of nondescent vaginal hysterectomy. Methods: This is a retrospective cohort study. 60 women who underwent nondescent vaginal hysterectomy in the department of OBG, B.G.S. Global Institute of Medical Sciences, Banglore, India were included in the study. Patients’ records were retrieved. Data regarding patient’s age, parity, indications for hysterectomy, uterine size in weeks, previous surgeries in the past, duration of surgery and complications were recorded. Data collected on a semi structured proforma and the same was analysed using suitable statistical analysis. Results: A total of 60 cases were operated for different indications. Among the study participants majority were in the age group of 41-45 years with 28 (46.7%). Most common indication for hysterectomies were dysfunctional uterine bleeding (DUB) with 27 (45%), followed by fibroid uterus 15 (25%). The mean duration of surgery time taken was 50+10minutes. Majority of the women who underwent hysterectomies had bulky uterus with 42 (70%). Complications were very few. Fever, UTI (urinary tract infection) and headache were seen in 3 (5%) cases. There was one case of vault sepsis and one case of upper respiratory tract infection (URTI). In one patient vaginal hysterectomy could not be completed and abdominal hysterectomy was carried out. Mean hospital duration was 4 days. Conclusions: Vaginal hysterectomy is the least invasive with fewer complications and most economical route for hysterectomy. Nondescent vaginal hysterectomy should be the gynaecologists first choice for hysterectomy.